Aplikasi Penyembunyian Pesan Pada File-File Dokumen Berekstenti .Xls/Xlsx Dengan Metode Modulus Function - Zai, Indarmawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Securing messages is a very important thing, because it avoids theft of important files from unauthorized parties. Steganography is a way of hiding messages or inserting messages into other media, so that other people do not know the authenticity of the information. A method is needed so that the data is not lost or is intact until it reaches its destination. In terms of data storage, security is needed so that the stored data cannot be opened, read or even taken by someone who does not have the right to try to open it. To be able to hide messages but not change the container that contains them, a steganography method is needed that can do this. The Modulus Function (MF) method is a message insertion technique that is carried out by modifying the residual value of the quotient (remainder). This method uses quantization of the gray value difference to determine the number of bits to be inserted at a certain value difference. The advantage of this modulus function method is that it is able to reduce changes in coefficient values ​​(coefficient adjustment) so that it is able to maintain the quality of the storage container. So it is in the testing stage with Binary viewer software. Can help in hiding messages in document files